Penerapan Media Augmented Reality Berbasis LKPD dengan Model Problem-Based Learning untuk Meningkatkan Pemahaman Konsep Struktur Mata Manusia Siswa Kelas V SD Negeri 2 Kembangbahu - Salsyabilah, Najwa; Zuhdi, Ulhaq (CV. Kurnia Grup, 2025)
This study aimed to describe the implementation and effectiveness of Augmented Reality (AR) media based on Student Worksheets (LKPD) using the Problem-Based Learning (PBL) model in improving students’ understanding of human eye structure concepts among fifth-grade students at SD Negeri 2 Kembangbahu. The research problem was based on students’ low conceptual understanding of human eye structure material, which is abstract in nature. This study employed Classroom Action Research using the Kemmis and McTaggart model conducted in two cycles, consisting of planning, implementation, observation, and reflection stages, with nine students as research subjects. Data were collected through tests, observations, interviews, and documentation and were analyzed using descriptive quantitative and qualitative techniques. The results showed that the implementation of LKPD-based AR media with the PBL model was carried out through five learning phases, namely problem orientation, student organization, investigation, presentation of results, and evaluation. Students’ conceptual understanding showed a significant improvement, as indicated by an increase in the average score from 55.55 in the pre-cycle to 75.55 in Cycle I and 97.77 in Cycle II, with classical mastery reaching 100%. In addition, students’ attitudes and skills were categorized as very good. Therefore, the integration of LKPD-based AR media with the PBL model was effective in concretizing abstract concepts and comprehensively improving students’ understanding of human eye structure.